The Effect of Debt to Asset Ratio, Firm Size, Audit Committee, and Audit Tenure on Audit Delay (on Property and Real Estate Sector Companies Listed on The Indonesia Stock Exchange for the 2016-2023 Period) - Setiawati, Lutfi; Febriyanti, Diah; Syarif, Devyanthi (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
Company, Debt to Asset Ratio (DAR), Audit Committee, and Audit Tenure. The research method used is quantitative with a descriptive and verification approach. Secondary data used were obtained from the annual financial reports for 2016-2023 in the property and real estate sector, accessed through the official pages of IDX and related companies. This study uses a purposive sampling technique, which resulted in 15 companies that met the criteria as research samples from a total population of 93 companies. The study's results indicate that audit tenure has a partially significant effect on audit delays. In contrast, DAR, company size, and audit committee do not have a partially significant effect on audit delays. However, simultaneously, the audit committee, audit tenure, company size, and debt-to-asset ratio affect audit delays.